Indicadores de sustentabilidade: estudo de caso em empresa de biotecnologia - Pires, Joelma da Costa Silveira (2016)
Sustainable development is the challenge of providing for the needs of the present without compromising future generations. Create tools that help this objective and that allows practices of the measurement within organizations is crucial to support the sustainability, the decision-making, the business management and also to achieving significant improvements to society, economy and environment. In this sense it is necessary to adapt sustainability indicators for visibility of information, to propose goals and specifics actions to optimize the operation and improvement of processes. Thus, this study has the general objective to develop a conceptual framework for the implementation of a set of sustainable indicators to a biotechnology business unit. The research was qualitative, case study type, and developed in a multinational company in the segment of life sciences, with a branch in Brazil. The company studied provides life science products and the main activity in Brazil is the sale of products and services. It was a document research, with participant observation and interviews with the company's leadership in order to identify the set of indicators corroborating corporate sustainability. It was found that although the company values sustainable initiatives, business management is done through performance indicators (KPI) and that most managers are unaware of the use of sustainability indicators as a corporate management tool.